Soelberg's Job Search and Choice Model: A Clarification, Review, and Critique - Power, Daniel; Aldag, Ramon J. (Academy of Management Review, 1985)
Soelberg (1966, 1967a, 1967b) developed a job search and choice model that is interpreted here as a four-phase, sequential process. An attempt is made to clarify the model, some of its hypotheses, and the measures used in Soelberg's research. Theoretical and practical implications of the model are presented; deficiencies of previous tests of the model are noted; and future research directions are suggested.